2008
DOI: 10.1007/s12245-008-0077-4
|View full text |Cite
|
Sign up to set email alerts
|

Pre-formatted written discharge summary—a step towards quality assurance in the emergency department

Abstract: BackgroundProviding discharge instructions to emergency department (ED) patients is not a standard practice and there is wide disparity in its implementation. There is evidence that ED discharge instructions, especially a pre- formatted one, complements verbal instructions and improves patient communication and management.AimsOur aim was to audit the practice of providing a discharge summary in a standardized pre-formatted form to patients visiting the ED at Sundaram Medical Foundation (SMF), Chennai, India.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…Overall, the results reflect the limited similar research from India that has evidenced unstructured and deficient HCP-patient communication at the point of discharge. [32,35] They are also consistent with other LMIC-based studies that, via patient reports and record evaluations, have evidenced a lack of in-depth information provision during discharge and/or poor levels of patient understanding regarding post-discharge care requirements. [27][28][29][30] The provision of deficient documented discharge information may be of particular concern for patient self-management, as global literature (predominantly from high-income countries) has indicated that individuals can struggle to absorb the verbal information provided by HCPs during healthcare consultations.…”
Section: Plos Onesupporting
confidence: 84%
See 2 more Smart Citations
“…Overall, the results reflect the limited similar research from India that has evidenced unstructured and deficient HCP-patient communication at the point of discharge. [32,35] They are also consistent with other LMIC-based studies that, via patient reports and record evaluations, have evidenced a lack of in-depth information provision during discharge and/or poor levels of patient understanding regarding post-discharge care requirements. [27][28][29][30] The provision of deficient documented discharge information may be of particular concern for patient self-management, as global literature (predominantly from high-income countries) has indicated that individuals can struggle to absorb the verbal information provided by HCPs during healthcare consultations.…”
Section: Plos Onesupporting
confidence: 84%
“…[64][65][66][67][68] Given the predominantly paper-based systems in use across the study settings, well-structured and standardised HCP checklists, documents and patient-held record booklets are also likely to advance the quantity and quality of essential information transferred between HCPs and between HCPs and patients and have proven successful in HIC and LMIC settings. [35,[69][70][71] Co-creation of such materials with HCPs, patients, carers and other key stakeholders should be considered in order to enhance acceptability, function and utilisation.…”
Section: Next Stepsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent (2019) study from South Africa has found inadequate discharge planning to be a significant contributor to avoidable causes of hospital readmission 13. Across India, a handful of predominantly single-site studies have evaluated and described deficiencies in information exchange during referrals, hospital shift change and discharge 14–19. The current study forms part of a series completed for a project investigating handover and continuity of care for patients with chronic NCDs in the states of Kerala and Himachal Pradesh in India.…”
Section: Introductionmentioning
confidence: 98%
“…Studies carried out in the emergency department (ED) setting have demonstrated that the provision of discharge information via a discharge summary in conjunction with verbal instructions improves both patient understanding of self-care at home and management of their medical issue (1)(2)(3)(4). Previously, discharge summaries and the provision of discharge instructions to patients being discharged from the ED was not a standardised practice in our institution.…”
Section: Introductionmentioning
confidence: 99%